Sonic velocity measurement in molten Pb–Li (16) at high temperature for ultrasonic flowmeter applications. (December 2022) - Sahu, S.; Bhope, K.; Prajapati, A.; Mehta, M.; Tailor, H.; Bhattacharyay, R.; Khirwadkar, S.S.
Abstract: An ultrasonic flowmeter can be a good alternate to electromagnetic flowmeter, being used extensively for high temperature liquid metals. It has an advantage of using it at any location and at any point of time. However, the usage of ultrasonic techniques in high temperature liquid metals is not well established, especially in molten Pb–Li. Pb–Li is considered as a potential coolant candidate in fusion reactor. To study the applicability of ultrasonic techniques in Pb–Li medium with a future scope to develop an ultrasonic flowmeter, a high temperature experimental facility was developed. Sonic velocity was measured in Pb–Li at temperatures ranging from 285 °C to 375 °C using the pulse echo method. It was observed that ultrasonic waves get highly attenuated in molten Pb–Li medium. Out of various tested ways, introduction of W reflector plate could provide detectable reflected signal. The proof of principle test was carried out on few liquids with known values of sonic velocity. The measured sonic velocities have a deviation of ∼6% from that of the reported values. Highlights: A novel measurement technique has been discussed for the measurement of sonic velocity in high temperature liquid meta. Process parameters affecting the ultrasonic signal strength of the reflected waves in Pb-Li has been studied. Sonic velocity measured in surrogate liquids and Pb-Li show accuracy of 6% from that of the reported data.